European Identity and Representations of the Other in Travel Literature: A Pictorial Reading of Pietro Della Valle's Texts on Safavid Iran - Hussein Ali Hassoon Alshammari (Peerian Journals Publishing, 2025)
This research aims to analyze representations of the Iranian other in the texts of the Italian traveler Pietro Della Valle (1586–1652), who visited the Safavid Empire between 1617 and 1623. This research relies on the method of literary imagery, which studies stereotypes and representations of the other in literary texts. The research is based on the premise that European travels to the East were not an objective reflection of reality, but rather narrative constructions that represented a means of reproducing European identity through a view of the Eastern other.
Keywords: Pietro Della Valle; European identity; literary imagery